2021
DOI: 10.3390/cancers13225678
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chromatin Dynamics and DNA Repair on Genomic Stability and Treatment Resistance in Pediatric High-Grade Gliomas

Abstract: Despite their low incidence, pediatric high-grade gliomas (pHGGs), including diffuse intrinsic pontine gliomas (DIPGs), are the leading cause of mortality in pediatric neuro-oncology. Recurrent, mutually exclusive mutations affecting K27 (K27M) and G34 (G34R/V) in the N-terminal tail of histones H3.3 and H3.1 act as key biological drivers of pHGGs. Notably, mutations in H3.3 are frequently associated with mutations affecting ATRX and DAXX, which encode a chaperone complex that deposits H3.3 into heterochromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 257 publications
0
10
0
Order By: Relevance
“…PNKP functions both in NHEJ and single-strand break repair pathways (Dumitrache and McKinnon, 2017) and altering both could support the synthetic growth defect observed. Since PNKP inhibition is already exploited to kill other cancers (Mereniuk et al, 2013), we suggest that it be used to sensitize pHGG cells to current radio/chemotherapeutic regimens (Pinto et al, 2021), for which there is very limited response. Moreover, the specificity towards H3.3 K27M and G34R mutant cells may limit toxicity-related side effects in future treatments and opens up the possibility of employing a similar strategy in other cancers bearing the same H3.3 mutations (Deshmukh et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PNKP functions both in NHEJ and single-strand break repair pathways (Dumitrache and McKinnon, 2017) and altering both could support the synthetic growth defect observed. Since PNKP inhibition is already exploited to kill other cancers (Mereniuk et al, 2013), we suggest that it be used to sensitize pHGG cells to current radio/chemotherapeutic regimens (Pinto et al, 2021), for which there is very limited response. Moreover, the specificity towards H3.3 K27M and G34R mutant cells may limit toxicity-related side effects in future treatments and opens up the possibility of employing a similar strategy in other cancers bearing the same H3.3 mutations (Deshmukh et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To study whether the observed DNA repair defect is mediated by analogous perturbations of histone PTMs, we reduced H3K27me3 and H3K36me3 by inhibiting or depleting the corresponding lysine methyltransferases. The H3K27 methyltransferase Enhancer of Zeste 2 (EZH2) is endogenously inhibited in U2OS cells (Jain et al, 2019;Ragazzini et al, 2019), thus preventing further reduction of H3K27me3 upon expression of H3.3 K27M (Figure S1B and S3D). Yet, aberrant DNA repair is still observed in H3.3 K27M U2OS cells (Figure 1A-B), arguing against a contribution of H3K27me3 reduction to this repair defect.…”
Section: Aberrant Nhej Is Independent Of H3k27/k36me3 Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced DNA repair pathways and chromatin dynamics are known to be associated with the development of MDR in tumor cells [ 9 , 17 , 19 ]. One recent clinical study illustrated the impact of DNA repair on genomic stability and resistance to the anticancer drug treatment of pediatric high-grade gliomas [ 20 ]. Cancer cells also become accustomed to hypoxic tissue conditions by overexpression of hypoxia-inducible factor-1α (HIF-1 α).…”
Section: Mechanisms Associated With Mdr In Cancermentioning
confidence: 99%
“…This observation is consistent with its role in increasing transcription (Park et al, 2016) and our pathway analysis results of human T-ALL cells cultured in the adipocyte secretome (Figure 2B; Supplementary Figure S3). Furthermore, H3.3 histones are deposited after DNA damage (Pinto et al, 2021), and the upregulation of H3F3A may result from the increased genomic instability observed in human T-ALL cells cultured in ACM (Figure 2B; Supplementary Figure S3). In addition, we observed that the gene expression levels of H2AFX were variable among ACM-cultured human T-ALL cells; whereas the H3F3B gene was expressed at similar levels under all conditions tested.…”
Section: The Adipocyte Secretome Induces Gene Expression Programs In ...mentioning
confidence: 99%